2008
DOI: 10.2174/1874318800802010068
|View full text |Cite
|
Sign up to set email alerts
|

Equine Herpes Virus-1: Virus, Immunity and Vaccines

Abstract: Equine Herpes virus-1 (EHV-1) is one of the most common respiratory pathogens of the horse. EHV-1 induces several clinical signs of disease ranging in severity, from mild respiratory distress to abortion in pregnant mares, neonatal foal death and neuropathogenic disorders. This review details some aspects of EHV-1 biology, its life cycle and pathogenicity in the natural host. Protective immunity stimulated by natural EHV-1 infection, which is short lived and depends of both humoral and cellular immune response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
7

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 114 publications
0
46
0
7
Order By: Relevance
“…Regardless of subfamily, most herpesviruses establish a post-inoculation systemic infection accompanied by a cell-associated viremia (virus present in the blood). In infected individuals, viremia is usually indicative of viral replication, and can be detectable during either the primary infection event or during viral reactivation following a period of latency (Paillot et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of subfamily, most herpesviruses establish a post-inoculation systemic infection accompanied by a cell-associated viremia (virus present in the blood). In infected individuals, viremia is usually indicative of viral replication, and can be detectable during either the primary infection event or during viral reactivation following a period of latency (Paillot et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Infection of umbilical cord blood can disseminate the virus in fetal organs. The secondary replication of EHV-1 in fetal tissues induces multi-organ infection with a variety of macroscopic and microscopic lesions (Edington et al 1991, Paillot et al 2008. Therefore, tissues of aborted fetuses, originating from the lungs, liver, spleen, heart, kidney, thymus and placenta appear to be the most suitable samples for testing.…”
Section: Discussionmentioning
confidence: 99%
“…However, this season specificity has not been observed in all countries. Paillot et al (2008) reported that neurological signs due to EHM were seen at an increased frequency in standard breeds, Hispanic breeds and draught breeds, with no cases of EHV-induced myeloencephalopathy in archetypical ponies, Haflinger, Fjord and Icelandic horses.…”
Section: Factors Affecting Ehmmentioning
confidence: 99%